2018
DOI: 10.1093/ecco-jcc/jjy005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is Associated with an Increased Risk of Microscopic Colitis: Results From Two Large Prospective Cohort Studies of US Women

Abstract: In two large prospective cohort studies, we observed an association between current smoking and risk of microscopic colitis. Risk of microscopic colitis appeared to increase with higher pack-years and diminish following smoking cessation. Future studies focused on characterizing the biological mechanisms underlying these associations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 63 publications
7
18
1
Order By: Relevance
“…We estimated that we would have an 80% power to detect a HR of at least 1.81 between the highest and lowest quintiles in a 2-tailed test. However, as previously reported in our cohort and consistent with prior studies (11, 28, 29), use of NSAIDs, PPIs, SSRIs, and smoking are strongly associated with risk of microscopic colitis, indicating that the contribution of gluten to the risk of microscopic colitis, if any, is minimal. Third, this study relied on self-reported questionnaires for assessing dietary gluten intake which may be subject to measurement errors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We estimated that we would have an 80% power to detect a HR of at least 1.81 between the highest and lowest quintiles in a 2-tailed test. However, as previously reported in our cohort and consistent with prior studies (11, 28, 29), use of NSAIDs, PPIs, SSRIs, and smoking are strongly associated with risk of microscopic colitis, indicating that the contribution of gluten to the risk of microscopic colitis, if any, is minimal. Third, this study relied on self-reported questionnaires for assessing dietary gluten intake which may be subject to measurement errors.…”
Section: Discussionsupporting
confidence: 92%
“…In both cohorts, a diagnosis of microscopic colitis was self-reported initially and was subsequently confirmed by two gastroenterologists (K.E.B, and H.K.) (11). Since 1976 in NHS and 1989 in NHSII, participants reported diagnoses of inflammatory bowel diseases, including microscopic colitis, ulcerative colitis, and Crohn’s disease during biennial questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…In a prior publication, the NHS reported a hazard ratio for tobacco smoking of 2.52 (1.59-4.00). 17 This result was similar to a previous odds ratio calculated for current tobacco use of 2.67 (1.38-5.17). 14 The similarity of these risk estimates from different studies again suggests but does not prove causality for MC.…”
supporting
confidence: 90%
“…LE: moderate; GR: NA; agreement: 100%, strong consensus Summary of evidence: the prevalence of current smoking in MC patients ranged from 15.3% to 40.7% (CC: 13.6-37.1%; LC: 13.2-26.0%) compared to 5.0-28.2% in non-MC control groups. 28,43,[73][74][75][76][77][78][79][80][81][82] In a recent meta-analysis, 83 current smokers had a significantly increased risk of MC compared with never smokers (odds ratio (OR) 2.99; 95% CI: 2.15-4.15). 83 Current smoking was more strongly associated with CC than LC (OR 5.5, 95% CI: 3.4-8.9; OR 2.96, 95% CI: 2.0-4.3, respectively).…”
Section: Epidemiology and Risk Factors Of MC What Is The Incidence Omentioning
confidence: 99%
“…[73][74][75][76]78,80,82 In two studies, current smokers developed MC more than one decade earlier than former or never smokers. 77,84 The majority of the studies showed no differences in terms of clinical presentation response to treatment, spontaneous remission rates and disease recurrence or need for maintenance treatment 73,75,77,78,81,[84][85][86][87][88][89] (see also Appendix D, supplementary material). Only in a post-hoc analysis of pooled data from two randomised controlled trials (RCTs) was current smoking associated with a decreased ability to achieve clinical remission with corticosteroid treatment (OR, 0.31; 95% CI: 0.10-0.98).…”
Section: Very Lowmentioning
confidence: 99%